2008
DOI: 10.1007/s10350-008-9326-0
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerve Stimulation for Fecal Incontinence: External Anal Sphincter Defect vs . Intact Anal Sphincter

Abstract: Sacral nerve stimulation for fecal incontinence is as effective in patients with external anal sphincter defects as those with intact sphincter and the result is similar for defect size up to 120 degrees of circumference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(88 citation statements)
references
References 32 publications
4
79
0
5
Order By: Relevance
“…After a median follow-up time of 36 (12-72) months, fecal incontinence scores dropped from a median of 15 (13)(14)(15)(16)(17)(18)(19)(20) preoperatively to a median of 5 (3)(4)(5)(6)(7) in all implanted patients (P Ͻ .01). Quality of life analysis for all implanted patients showed significant improvement in all 4 domains (lifestyle, coping behavior, depression, and embarrassment (P Ͻ .01)).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…After a median follow-up time of 36 (12-72) months, fecal incontinence scores dropped from a median of 15 (13)(14)(15)(16)(17)(18)(19)(20) preoperatively to a median of 5 (3)(4)(5)(6)(7) in all implanted patients (P Ͻ .01). Quality of life analysis for all implanted patients showed significant improvement in all 4 domains (lifestyle, coping behavior, depression, and embarrassment (P Ͻ .01)).…”
Section: Resultsmentioning
confidence: 97%
“…1 SNM has repeatedly been shown to be a successful treatment option for patients suffering from fecal incontinence of different indications. [5][6][7] Even on the basis of controlled randomized trials, this therapy has shown high efficacy and low morbidity, and can be regarded as an effective treatment for fecal incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies support anal manometry and endoanal ultrasonography in guiding treatment options in patients with FI [19,20]. However, other studies suggest that findings on physiology testing do not consistently correlate with severity of FI or prediction of outcome [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al 19 , con un seguimiento de 12 meses, presentaron un 15% de complicaciones menores. Se ha visto que a mayor seguimiento, mayores son las complicaciones descritas.…”
Section: Fase De Implantación Del Generador Definitivounclassified